INSTAGRAM KOMUNITAS STANDUPINDO SERANG - Bintang, Muhammad Ilham (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2024)
Instagram StandupIndo Serang Community strives to provide useful and relevant content, entertainment, or information to engaged audiences on social media platforms, with the aim of strengthening engagement, building trust, and expanding the reach of influence in the digital environment. This concept emphasizes the importance of making a positive contribution to the online community, as well as strategies to meet the needs and interests of community members in order to build sustainable relationships and meaning.Instagram Komunitas StandupIndo Serang  berupaya untuk menyediakan konten, hiburan, atau informasi yang bermanfaat dan relevan bagi audiens yang terlibat di platform media sosial, dengan tujuan memperkuat keterlibatan, membangun kepercayaan, dan memperluas jangkauan pengaruh dalam lingkungan digital. Konsep ini menekankan pentingnya kontribusi positif terhadap komunitas online, serta strategi untuk memenuhi kebutuhan dan minat anggota komunitas dalam rangka membangun hubungan yang berkelanjutan dan berarti.